Brief Report: Emotion Regulation Influences on Internalizing and Externalizing Symptoms Across the Normative-Clinical Continuum - Cai, Ru Ying; Hardan, Antonio Y.; Phillips, Jennifer M.; Frazier, Thomas W.; Uljarević, Mirko (Frontiers in Psychiatry, 2021)
Emotion regulation is theorized to be a transdiagnostic process and has been empirically shown to be associated with various mental health and neurodevelopmental conditions. However, the relationship between emotion regulation and internalizing and externalizing symptoms has yet to be characterized in a sample of individuals spanning normative and atypical development. Therefore, this study aimed to provide initial evidence for emotion regulation as a transdiagnostic process of internalizing and externalizing symptoms in a community sample of adolescents with and without neuropsychiatric and neurodevelopmental conditions. The sample consisted of 1,705 caregivers of adolescents aged between 11 and 17 years (Mage = 14.53, SDage = 1.96). Adolescents were typically developing or had a caregiver-reported diagnosis of autism spectrum disorder, attention-deficit hyperactivity disorder, or anxiety. The typically developing adolescents had significantly better caregiver-reported emotion regulation than adolescents with caregiver-reported neuropsychiatric and neurodevelopmental. Additionally, emotion dysregulation significantly and positively correlated with and predicted internalizing and externalizing symptoms within each subgroup. Importantly, emotion dysregulation had a unique contribution to individual differences in the severity of internalizing and externalizing symptoms, above and beyond the diagnostic status. The research and translational implications of the study findings are discussed.